No thank you to humanized robots: attitudes to care robots in elder care services. Issue 1 (2nd January 2022) - Johansson-Pajala, Rose-Marie; Zander, Viktoria; Gustafsson, Christine; Gusdal, Annelie
ABSTRACT: The growing older population will increase the demands on the health and welfare systems, including elder care services. One way of meeting these growing service needs is to shift from traditional care services to technologically oriented services. Robotic innovations are gradually being introduced to elder care services. The aim was to explore attitudes toward the use of care robots in elder care services – specifically focusing on situations and interaction, influence, and emotions in interaction with care robots. Data were obtained from visitors at a welfare technology fair ( n = 124). The results show that the most negative attitudes concerned if the care robots were humanized and had emotions. The attitudes toward interacting with care robots in general were predominately positive. In conclusion, concrete usage scenarios in elder care services need to be detected, based both on users' needs, digital literacy and on the maturity of the technology itself.